SYMBOLISM AND SOCIAL CLASS CONFLICT IN ”THE PLATFORM” : A QUALITATIVE CONTENT ANALYSIS - Fitria, Ajeng Noor; Probowati, Yeni; Kuswahono, Deny (Universitas PGRI Sumatera Barat, 2024)
This study provides a comprehensive analysis of the film